PEMANFAATAN SAMPAH ORGANIK UMKM UNTUK MEDIA TANAM BERBASIS KOMPOSTING - Teuku Muhammad Rasyif; Asiah Nurul; Adriati Fatin; Syalwa Linda Hilmayani; Faiz Aly; Andyni Clarissa Hartono (LPPM Institut Pendidikan Nusantara Global, 2025)
Food waste has become a critical global issue with significant environmental, social, and economic consequences. This community service program focused on empowering micro, small, and medium enterprises (MSMEs) at Pujasera JS09 in Jakarta to manage organic waste through composting. The program identified that the canteen produced an average of 150–200 kg of food waste daily, of which 10–30 kg consisted of vegetable residues, fruit peels, and other organic materials suitable for composting. Using a roller composter, the decomposition process successfully transformed waste into mature planting media within approximately 16 days. Compost maturity was confirmed through pH stabilization at 7, neutral odor, and positive immersion tests. Furthermore, carbon footprint analysis using the EPA WARM model revealed that diverting 20 kg/day of organic waste from landfills to composting reduced greenhouse gas emissions by 3.06 tons CO₂e annually, equivalent to an 8% reduction. These results highlight that composting not only improves local hygiene and reduces methane emissions but also supports sustainable waste management practices and climate change mitigation. The program demonstrates a practical and replicable approach for MSMEs to contribute to circular economy implementation and environmental sustainability.